2021
DOI: 10.3390/molecules26092608
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Polysaccharide Based Products and Materials: An Assessment on Their Production from a Sustainability Point of View

Abstract: Among the various natural polymers, polysaccharides are one of the oldest biopolymers present on the Earth. They play a very crucial role in the survival of both animals and plants. Due to the presence of hydroxyl functional groups in most of the polysaccharides, it is easy to prepare their chemical derivatives. Several polysaccharide derivatives are widely used in a number of industrial applications. The polysaccharides such as cellulose, starch, chitosan, etc., have several applications but due to some disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 143 publications
0
25
0
Order By: Relevance
“…Marine pharmacologist creates methods in the manufacturing business that maximize the yield and production rate of FA. They also want to cut waste and energy expenses at every step of the experiment [ 23 ]. The agar formulation methods and yield used for developing antioxidant properties for both the FAs from brown seaweed have been successful ( T. conoides ).…”
Section: Resultsmentioning
confidence: 99%
“…Marine pharmacologist creates methods in the manufacturing business that maximize the yield and production rate of FA. They also want to cut waste and energy expenses at every step of the experiment [ 23 ]. The agar formulation methods and yield used for developing antioxidant properties for both the FAs from brown seaweed have been successful ( T. conoides ).…”
Section: Resultsmentioning
confidence: 99%
“…Seaweed polysaccharide is one of the important active components of traditional Chinese medicine seaweed. The well-known fucoidan, agarose, carrageenan, alginic acid, ulvan and fucoidan all belong to seaweed polysaccharide ( Chudasama, Sequeira, Moradiya, & Prasad, 2021 ), as shown in Fig. 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The experiments conducted by the Qingdao Ocean University demonstrated that LMSF can directly scavenge peroxyanion free radicals and hydroxyl free radicals in vitro and also significantly enhance the SOD binding capacity in serum and tissues in vivo . Accordingly, it can serve as a potential drug in lowering blood lipids and preventing atherosclerosis [ 8 , 9 ]. The present study was designed to explore the treatment effectiveness of double-heart nursing in combination with seaweed polysaccharide on coronary heart disease complicated with diabetes.…”
Section: Introductionmentioning
confidence: 99%